Table of Contents
Last modified on January 30th, 2025
Reciprocal identities express the inverse relationships between the six trigonometric functions: sine, cosine, tangent, cosecant, secant, and cotangent.
Here are the three basic trigonometric functions, sine, cosine, and tangent, and their relation to their reciprocals:
Sine is the reciprocal of cosec and vice versa.
Cosine is the reciprocal of sec and vice versa.
Tangent is the reciprocal of cotangent and vice versa.
Here, we will consider a right-angled triangle ABC, which is right-angled at C, to derive the reciprocals.
From the triangle ABC,
sin θ = ${\dfrac{b}{c}}$ = ${\dfrac{Opposite \ side}{Hypotenuse}}$
As we know,
The reciprocal of ${\dfrac{b}{c}}$ is ${\dfrac{c}{b}}$
⇒ ${\dfrac{c}{b}}$ = ${\dfrac{Hypotenuse}{Opposite \ side}}$ = cosec θ
Thus, sin θ is the reciprocal of cosec θ and vice-versa.
Similarly, from the triangle ABC,
cos θ = ${\dfrac{a}{c}}$ = ${\dfrac{Adjacent \ side}{Hypotenuse}}$
As we know,
The reciprocal of ${\dfrac{a}{c}}$ is ${\dfrac{c}{a}}$
⇒ ${\dfrac{c}{a}}$ = ${\dfrac{Hypotenuse}{Adjacent \ side}}$ = sec θ
Thus, cos θ is the reciprocal of sec θ and vice-versa.
Again, from the triangle ABC,
tan θ = ${\dfrac{b}{a}}$ = ${\dfrac{Opposite \ side}{Adjacent \ side}}$
As we know,
The reciprocal of ${\dfrac{b}{a}}$ is ${\dfrac{a}{b}}$
⇒ ${\dfrac{a}{b}}$ = ${\dfrac{Adjacent \ side}{Opposite \ side}}$ = cot θ
Thus, tan θ is the reciprocal of cot θ and vice-versa.
The product of a trigonometric function and its reciprocal is always equal to 1:
Find: cosec θ if sin θ = ${\dfrac{3}{5}}$
As we know, cosec θ is the reciprocal of sin θ
Here, ${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$ and sin θ = ${\dfrac{3}{5}}$
Thus, cosec θ = ${\dfrac{5}{3}}$
Find the value of cot 60° if tan 60° = ${\sqrt{3}}$
As we know, cot θ is the reciprocal of tan θ
Here, cot 60° = ${\dfrac{1}{\tan 60^{\circ }}}$ and tan 60° = ${\sqrt{3}}$
Thus, cot 60° = ${\dfrac{1}{\sqrt{3}}}$
The reciprocal trigonometric functions can also be used to simplify complex mathematical expressions.
Simplify: ${\dfrac{\tan \theta \sec \theta }{\cot \theta \text{cosec}\, \theta }}$
By expressing the reciprocal functions in terms of sine and cosine, we get
${\sec \theta =\dfrac{1}{\cos \theta }}$, ${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$, ${\tan \theta =\dfrac{\sin \theta }{\cos \theta }}$, and ${\cot \theta =\dfrac{\cos \theta }{\sin \theta }}$
Now, by substituting these values into the expression, we get
${\dfrac{\tan \theta \sec \theta }{\cot \theta \text{cosec}\, \theta }}$
= ${\dfrac{\dfrac{\sin \theta }{\cos \theta }\cdot \dfrac{1}{\cos \theta }}{\dfrac{\cos \theta }{\sin \theta }\cdot \dfrac{1}{\sin \theta }}}$
= ${\dfrac{\dfrac{\sin \theta }{\cos ^{2}\theta }}{\dfrac{\cos \theta }{\sin ^{2}\theta }}}$
= ${\dfrac{\sin \theta }{\cos ^{2}\theta }\cdot \dfrac{\sin ^{2}\theta }{\cos \theta }}$
= ${\dfrac{\sin ^{3}\theta }{\cos ^{3}\theta }}$
= ${\tan ^{3}\theta}$
On graphing the reciprocal functions, we get
Here,
These undefined points correspond to the vertical asymptotes of their respective graphs, as shown.
Find the values of the following reciprocal trigonometric functions:
a) ${\text{cosec}\, \dfrac{\pi }{4}}$ when ${\sin \dfrac{\pi }{4}=\dfrac{\sqrt{2}}{2}}$
b) ${\sec \dfrac{\pi }{3}}$ when ${\cos \dfrac{\pi }{3}=\dfrac{1}{2}}$
c) ${\tan \dfrac{\pi }{4}}$ when ${\cot \dfrac{\pi }{4}=1}$
a) As we know, sine and cosecant are reciprocal functions.
${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$
Here, ${\text{cosec}\, \dfrac{\pi }{4}}$
= ${\dfrac{1}{\sin \dfrac{\pi }{4}}}$
= ${\dfrac{1}{\dfrac{\sqrt{2}}{2}}}$
= ${\dfrac{2}{\sqrt{2}}}$
= ${\sqrt{2}}$
Thus, ${\text{cosec}\, \dfrac{\pi }{4}}$ = ${\sqrt{2}}$
b) As we know, cosine and secant are reciprocal functions.
${\sec \theta =\dfrac{1}{\cos \theta }}$
Here, ${\sec \dfrac{\pi }{3}}$
= ${\dfrac{1}{\cos \dfrac{\pi }{3}}}$
= ${\dfrac{1}{\dfrac{1}{2}}}$
= ${2}$
Thus, ${\sec \dfrac{\pi }{3}}$ = ${2}$
c) As we know, tangent and cotangent are reciprocal functions.
${\tan \theta =\dfrac{1}{\cot \theta }}$
Here, ${\tan \dfrac{\pi }{4}}$
= ${\dfrac{1}{\cot \dfrac{\pi }{4}}}$
= ${\dfrac{1}{1}}$
= ${1}$
Thus, ${\tan \dfrac{\pi }{4}}$ = ${1}$
Evaluate: ${\dfrac{\cos \theta }{\sin \theta }\times \text{cosec}\, \theta \times \sec \theta}$
Here, ${\dfrac{\cos \theta }{\sin \theta }\times \text{cosec}\, \theta \times \sec \theta}$
= ${\dfrac{\cos \theta }{\sin \theta }\times \dfrac{1}{\sin \theta }\times \dfrac{1}{\cos \theta }}$
= ${\dfrac{1}{\sin \theta }\times \dfrac{1}{\sin \theta }}$
= ${\dfrac{1}{\sin ^{2}\theta }}$
= ${\text{cosec}\, ^{2}\theta}$
Thus, ${\dfrac{\cos \theta }{\sin \theta }\times \text{cosec}\, \theta \times \sec \theta}$ = ${\text{cosec}\, ^{2}\theta}$
Prove the identity: cosec2 θ – cot2 θ = 1
Here, cosec2 θ – cot2 θ
= ${\dfrac{1}{\sin ^{2}\theta }-\dfrac{\cos ^{2}\theta }{\sin ^{2}\theta }}$
= ${\dfrac{1-\cos ^{2}\theta }{\sin ^{2}\theta }}$
= ${\dfrac{\sin ^{2}\theta }{\sin ^{2}\theta }}$ (From the identity, sin2 θ + cos2 θ = 1)
= ${1}$
Thus, cosec2 θ – cot2 θ = 1, proved.
Simplify the expression: ${\dfrac{\sec ^{2}\theta -\tan ^{2}\theta }{\text{cosec}\, ^{2}\theta -\cot ^{2}\theta }}$
Here, ${\dfrac{\sec ^{2}\theta -\tan ^{2}\theta }{\text{cosec}\, ^{2}\theta -\cot ^{2}\theta }}$
Using Pythagorean identities, 1 + tan2 θ = sec2 θ and 1 + cot2 θ = cosec2 θ,
= ${\dfrac{1+\tan ^{2}\theta -\tan ^{2}\theta }{1+\cot ^{2}\theta -\cot ^{2}\theta }}$
= ${\dfrac{1}{1}}$
= ${1}$
Thus, ${\dfrac{\sec ^{2}\theta -\tan ^{2}\theta }{\text{cosec}\, ^{2}\theta -\cot ^{2}\theta }}$ = ${1}$
Last modified on January 30th, 2025